2022
DOI: 10.1002/hep4.1984
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the editor: The clinically relevant MTARC1 p.Ala165Thr variant impacts neither the fold nor active site architecture of the human mARC1 protein

Abstract: A study recently published in Hepatology Communications provided insights into a variant of MTARC1 protein, which conveys protection against liver disease. Here, we report a crystal structure of the variant protein at near‐atomic resolution and compare it to the structure of the wildtype protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…However, as the impact of missense variants in MTARC1 on protein levels, localisation, and activity is unclear, the directional effect of MTARC1 can only be inferred from the rare loss of function variant encoding a premature stop codon (p.R200Ter, rs139321832:C:T). 30 Using MR, we demonstrated that increased MTARC1 mRNA was associated with adverse effects on metabolic traits. Although the tissues with available eQTLs (muscle, left heart ventricle, and rectum) may not contribute to the associated phenotypes, the concordant effect direction indicates a consistent impact of the gene variants on gene expression across tissues.…”
Section: Discussionmentioning
confidence: 95%
“…However, as the impact of missense variants in MTARC1 on protein levels, localisation, and activity is unclear, the directional effect of MTARC1 can only be inferred from the rare loss of function variant encoding a premature stop codon (p.R200Ter, rs139321832:C:T). 30 Using MR, we demonstrated that increased MTARC1 mRNA was associated with adverse effects on metabolic traits. Although the tissues with available eQTLs (muscle, left heart ventricle, and rectum) may not contribute to the associated phenotypes, the concordant effect direction indicates a consistent impact of the gene variants on gene expression across tissues.…”
Section: Discussionmentioning
confidence: 95%
“…MTARC1 is a molybdenum‐containing enzyme with reductive activity on n‐oxygenated compounds 33 . The exact functional consequences of the MTARC1 p.A165T polymorphisms are yet to be defined 34 . The second known genetic variant HSD17B13 rs72613567 is associated with protection against hepatic fat accumulation 20 .…”
Section: Discussionmentioning
confidence: 99%
“…33 The exact functional consequences of the MTARC1 p.A165T polymorphisms are yet to be defined. 34 The second known genetic variant HSD17B13 rs72613567 is associated with protection against hepatic fat accumulation. 20 Recent findings have demonstrated that selective targeting of HSD17B13 mRNA in hepatocytes might be a promising therapeutic approach in NASH.…”
Section: Discussionmentioning
confidence: 99%
“…The only MOSC domain protein crystal structures are those of human mARC1 7 and its disease-related p.A165T variant. 23 However, in these structures, there is only partial occupancy of the Mo ion and the exact coordination environment about the Mo ion is not clearly defined. The structure of plant mARC1 in the oxidized Mo(VI) state has been interrogated by X-ray absorption spectroscopy (XAS).…”
mentioning
confidence: 99%
“…Unfortunately, no crystal structure of E. coli YcbX has been published and no spectroscopic data on the molybdenum active site are available, further complicating the development of structure–property relationships among MOSC family enzymes. The only MOSC domain protein crystal structures are those of human mARC1 and its disease-related p.A165T variant . However, in these structures, there is only partial occupancy of the Mo ion and the exact coordination environment about the Mo ion is not clearly defined.…”
mentioning
confidence: 99%